Становлення присвійного займенника третьої особи множини в українській літературній мові - Шведова, М.О. (Мовознавство, 2018)
У статті розглянуто функціонування присвійних займенників третьої особи множини їх і їхній в українській мові ХІХ–ХХІ ст. Дослідження здійснено на базі Генерального регіонально анотованого корпусу української мови. До 1870-х рр. варіант їхній не зафіксовано в текстах корпусу і до початку ХХ ст. його вживали мало. У 20–30 рр. варіант їхній стає значно поширенішим у літературі, словники ХХ ст. його підтримують і він закріплюється в узусі. На початку ХХІ ст. спостерігаємо збільшення частки вживання присвійного займенника їх у нехудожніх текстах, хоч основним варіантом залишається їхній, у художніх текстах їхній також домінує. The paper describes the diachronic evolution of the specialized (adjectival) possessive
jixnij ‘their’ in Ukrainian, as opposed to the invariable possessive jix, ambiguous between
possessive and pronominal genitive. The latter pattern is the only standard variant in
Russian, whereas in Ukrainian and Belarusian a certain degree of variation between the
two models is attested, distinctive also from the diachronic point of view. The study is
based on GRAC, a diachronic regionally annotated Ukrainian corpus including texts since
the arrival of the Modern Ukrainian period (1810s) until the present-day texts. Different
regions of Ukraine are represented in the corpus, as well as different countries of the
diaspora. The occurrence of both variants is statistically analyzed depending upon the
corresponding periods and regions. Before 1870s jixnij is not attested in the works of the major Ukrainian writers of
the period. It was still used rather marginally in the last quarter of the 19th century, with
Mykhajlo Starytskyj as the first author to use it on a par with the possessive jix. Jixnij does
not gain ground until the 20th century, the first author to use it predominantly over jix being
Volodymyr Vynnychenko. Something it is characterized by the linguists of the period as a
neologism or Russianism (ostensibly from Russian non-standard ixnij and its variants). It becomes first standardized as the preferable option, more clearly disambiguating between the genitive and the possessive function, about 1920s–1930s, and becomes widespread
after that date. The normative sources of the 20th century hesitate between the two,
although, in its second half, increasingly prefer jixnij. The usage basically follows the
norm, and currently numerous purists, vice versa, tend to reject and stigmatize the older
variant jix as an alleged Russianism and/or neologism. Even the texts of the 19th century
are sometimes re-edited with jix changed to jixnij. Our study shows that jixnij is used overall less frequently (in all the historical
periods) in non-fiction than in fiction, and that the dramatic increase in its frequency
occurs about 1970 in fiction but only about 1990 in non-fiction. Some regional differences
between Eastern and Western Ukraine are not so clear-cut. Jix also tends to retain higher
frequencies within idioms like jix(nja) mylist’/velyčnist’ ‘their grace/majesty’ than in free
combinations. In journalistic, official and academic texts the rate of jixnij increases slower and in
combination with specific lexicon rare in fiction and oral speech like zmist ‘content’,
značennja ‘meaning’, osnova ‘basis’ etc. fluctuates about 50% of all the 3rd person singular
possessives in the texts created after 1945; currently it is even lower than 50%. Thus the
new variant jixnij is the unmarked one and the most frequent one in the contemporary
texts, being used in different genres, whereas the older variant jix is restricted in its use
while still clearly regaining ground in non-fiction.